PERFORMANCE ANALYSIS OF A THERMOELECTRIC GENERATOR (TEG) INTEGRATED INTO A BIOMASS STOVE USING A CONTINUOUS COOLING SYSTEM - Hulam Darojati; Imron Rosyadi; Ni Ketut Caturwati; Hery Try Waloyo (Magister Teknik Mesin Universitas Pancasila, 2026)
This study aims to analyze the performance of a SP1848-27145 SA Thermoelectric Generator (TEG) integrated into the wall of a biomass stove as a small-scale alternative power generation system. The primary objective is to evaluate the effect of implementing a continuous cooling mechanism on the temperature difference (∆T) and the electrical power output. The research was conducted experimentally by varying three main parameters, namely the cooling method, the mass of wood biomass fuel, and the number of TEG modules. The experimental results indicate that continuous cooling using ice-water as the cooling medium provides the most optimal thermal performance, maintaining the cold-side temperature (Tc) as low as 17°C–21°C and producing a maximum temperature difference (∆T) of 54.07°C. The highest electrical performance was achieved using a configuration of two TEG modules connected in series with a 400 g fuel load and ice-water cooling, generating an output voltage of 2.14 V and electrical power of 0.47 W. This performance is nearly four times higher than that obtained using a single TEG module. Furthermore, the efficiency of the two-module TEG system with ice-water cooling reached 3.63%, which is higher than the efficiency of the two-module configuration without cooling, which was only 2.21%.